2020
DOI: 10.1016/j.jmoldx.2020.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Roche cobas MTB Assay for the Molecular Diagnosis of Pulmonary Tuberculosis in a High HIV Burden Setting

Abstract: Disclosures: L.S. reports having a patent issued (USP 8709712) that relates to quality control material and program for molecular TB diagnostics quality management. Roche Molecular Solutions provided funding but did not have any input in the study design or presentation of results contained in the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
(45 reference statements)
0
7
3
Order By: Relevance
“…Our study demonstrates that the cobas MTB assay meets the minimal performance characteristics stated in the WHO target product profile for a same-day diagnostic test detecting pulmonary TB as an alternative to smear microscopy, which is a sensitivity of >80% (smear-negative samples, >60%; smear-positive samples, 99%) and a specificity of >98% compared with culture ( 22 ). We observed that the overall sensitivity of cobas MTB (89.2%; 95% CI, 81.7 to 93.9%) was lower than in a study by Scott et al, who reported an overall sensitivity of 94.7% (95% CI, 88.1 to 98.3%) using decontaminated sputum sediments from individuals with presumptive or confirmed TB in South Africa ( 16 ). However, the proportion of smear-negative, culture-positive samples in our study was significantly larger (26.5% versus 7%) ( 16 ).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Our study demonstrates that the cobas MTB assay meets the minimal performance characteristics stated in the WHO target product profile for a same-day diagnostic test detecting pulmonary TB as an alternative to smear microscopy, which is a sensitivity of >80% (smear-negative samples, >60%; smear-positive samples, 99%) and a specificity of >98% compared with culture ( 22 ). We observed that the overall sensitivity of cobas MTB (89.2%; 95% CI, 81.7 to 93.9%) was lower than in a study by Scott et al, who reported an overall sensitivity of 94.7% (95% CI, 88.1 to 98.3%) using decontaminated sputum sediments from individuals with presumptive or confirmed TB in South Africa ( 16 ). However, the proportion of smear-negative, culture-positive samples in our study was significantly larger (26.5% versus 7%) ( 16 ).…”
Section: Discussioncontrasting
confidence: 82%
“…MTBC DNA-positive samples are subsequently tested for resistance-associated mutations, which allows for diagnosis of RIF or INH monoresistance as well as MDR-TB. Limited data are available for the performance of the cobas MTB and MTB-RIF/INH assays compared to culture and other commercially available NAATs ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in South Africa, in a high-HIV-burden setting, also reported that the Roche cobas MTB, Abbott RealTi m e MTB, and Xpert MTB/RIF assays ( n = 294) have similar performances of 94.7% (95% CI, 88% to 98%), 92.6% (95% CI, 85% to 97%), and 91.6% (95% CI, 84% to 96%), respectively. These assays also performed similarly among smear-negative, culture-positive individuals ( n = 221): 81.8% (95% CI, 60% to 95%), 72.7% (50% to 89%), and 72.7% (50% to 89%), respectively ( 11 ).…”
Section: Discussionmentioning
confidence: 87%
“…Published data from clinical studies to date demonstrate promising diagnostic performances of these assays when used in the appropriate scenarios ( 8 11 ). However, most of the available studies have important limitations.…”
Section: Introductionmentioning
confidence: 99%